2015
DOI: 10.5812/jjm.19698
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hepatitis B and C Viruses, and HIV Among Drug Addicts in the Eastern Anatolia, Turkey

Abstract: Background:Hepatitis B, hepatitis C and HIV infections constitute serious healthcare problems worldwide.Objectives:There are a limited number of studies regarding the prevalence of hepatitis B, hepatitis C and HIV infections among the drug addicts in Turkey; hence, the current study aimed to determine the frequency of these infections among 235 drug addicts treated in a drug addiction treatment centre/Elazig, Turkey.Patients and Methods:HBsAg, anti-HBs, anti-HCV and anti-HIV tests in 235 drug addicts were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In another study at Eastern Anatolia, Turkey in 2015 has observed the frequencies of HBsAg and anti-HCV among drug addicts were 2.6% 13 and 9.4%, respectively which is comparable with our study, in the said research, no HIV positive was found among drug users but in our scenario the HIV is more prevalent. A study from Quetta Pakistan has shown the frequency of HBV, HCV and HIV among IDUs as 43%, 44.7% and 0.33% 14 respectively, which is somehow comparable with ours though the morbidity of HBV and HCV in our study is lower than that.…”
Section: Discussionsupporting
confidence: 90%
“…In another study at Eastern Anatolia, Turkey in 2015 has observed the frequencies of HBsAg and anti-HCV among drug addicts were 2.6% 13 and 9.4%, respectively which is comparable with our study, in the said research, no HIV positive was found among drug users but in our scenario the HIV is more prevalent. A study from Quetta Pakistan has shown the frequency of HBV, HCV and HIV among IDUs as 43%, 44.7% and 0.33% 14 respectively, which is somehow comparable with ours though the morbidity of HBV and HCV in our study is lower than that.…”
Section: Discussionsupporting
confidence: 90%
“…Clinical data were assessed in accordance with the test results of viral parameters of probation cases which were sent to the serology laboratory retrospectively. From the serum samples, HBsAg was examined in 4357 cases aging between 14-71 (mean+SD 30±9), anti-HCV was examined in 4451 cases aging between 17-74 (mean+SD 30.01±9) and anti-HIV was examined in 4464 cases aging between 17…”
Section: Materials and Applicationmentioning
confidence: 99%
“…In our previous study performed between September 2011 and October 2012, HBsAg, anti-HBs and anti-HCV frequency in drug addicts were found to be 2.6%, 38.3% and 9.4%, respectively. Additionally, anti-HIV positivity was not detected (1). The present study showed that the frequency rate of HBsAg, anti-HBs and anti-HCV in drug addicts was 4%, 52.3% and 7.9%, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Cannabis is the most consumed drug in the world (1). Cannabis or marijuana contains the psychoactive chemical delta-9-tetrahydrocannabinol, which is believed to be the main chemical component that produces the psychoactive effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation